Stability analysis for quality attributes in durum wheat (Triticum durum L.) genotypes - Punia, Himani; Madan, Shashi; Malik, Anurag; Sethi, S.K. (Bangladesh Journal of Botany, 2019)
Wheat contributes more than 50% of calories to the people worldwide. In terms of appearance, colour, texture and flavor, the quality is determined by raw material, processing methods and other ingredients. The glutenin and gliadin proteins influence dough properties. Thirty-six durum wheat genotypes were evaluated for various quality traits viz. grain appearance score, grain hardness, sedimentation value and wet and dry gluten content. The superior genotypes for the physical characteristics of grains were PDW 337, UAS 448 and PDW 335. Wet and dry gluten were maximum in UAS 448 and WHD 954. PDW 337 (44 ml) and DDW 27 (44 ml) had highest sedimentation value. Present study reveals the identification of superior durum wheat genotypes which may be used in future breeding programmes to enhance the quality for human nutrition and specific end-uses.